METODE DRILL TERHADAP KEMAMPUAN MENGGOSOK GIGI ANAK TUNANETRA DI SDLB-A - Laili Rahmawahti, Noer (Jurnal Pendidikan Khusus, 2017)
Abstract     The blind children experienced hindrance in self guide especially in brushing teeth. From the result of early observation in SDLB-A YPAB Tegalsari Surabaya there were 6 blind children whose self guide ability of brushing teeth was low enough because in the daily activity they were still helped by other people or parents. One of the learning methods which could be used to enhance brusing teeth ability of blind children was drill method. Therefore, the purpose of this research was to prove whether there was influence of drill method toward brushing teeth ability to blind children in SDLB-A YPAB Tegalsari Surabaya or not. The research design used quantitative approach with pre experiment kind, one group pre-test post-test design. The data was collected using early observation, last observation, and documentation. The research was implemented in ten times meeting i.e.: once pre-test, once post-test, and eight times treatment. The data was then analyzed using Wilcoxon Match Pairs Test formula. The research result indicated that before giving treatment the average obtained was 56,9 and after giving treatment the average obtained was 79,1 so it could be concluded that there was influence of drill method toward brushing teeth ability to blind children in SDLB-A YPAB Tegalsari Surabaya (Zh = 2,20 > Zt = 1,96).     Keywords: Drill method, brushing teeth